Enlightenment to Floating Tunnel of Existing Typical Submerged Tunnel. (2016) - Hao, Ding; Qinxi, Li; Shuping, Jiang; Ke, Li
Abstract: Currently, submerged floating tunnel still stays in scientific research stage, while many submerged tunnels have been built by use of borehole-blasting method, shield method, immersed tube method and other traditional construction methods. This paper, through wide literature research and engineering data collection, analyzes construction environment limits and typical operating diseases of submerged tunnels for various traditional construction methods, and, specific to the eight typical major water areas including Taiwan Strait, Qiongzhou Strait, Bohai Strait, Bering Strait, and Messina Strait, discusses and analyzes enlightenment to floating tunnel project of existing submerged tunnel: (1) For submerged tunnels using traditional construction method, only from the point of view of construction environment limits, existing construction experience and technology have already been not suitable for 50∼87.5% of typical major water areas, technical breakthrough or innovation is required, while floating runnel will be one of the effective options for these water areas. (2) For construction of submerged tunnels in part of major water area, combination of traditional construction method+floating method will be one effective method. (3) Water leakage, lining material degradation and rebar corrosion and expansion and other diseases and specific difficulties in maintainability and durability of structure and connection components for submerged tunnels using traditional construction method will be main operating diseases for floating tunnel.